An IoT Platform for Vehicle Traffic Monitoring System and Controlling System Based on Priority - Nagmode, Varsha Sahadev; Rajbhoj, S.M. (2017 International Conference on Computing, Communication, Control and Automation (ICCUBEA), 2017)
In recent years traffic congestion is a major problem in our country, which affects modern city's daily life routine and disturb environments. Due to increase population, size of cities expands, automatically number of vehicles increases in the major scale on roads. There are many problems such as travel time delay, fuel wastage, air pollution and create issues related to transport. So traffic monitoring and controlling is the biggest challenge on traffic management authorities. We design and develop system for real-time traffic monitoring using Internet of Things (IoT) platform and sensing technology. In this system, Ultrasonic sensors are used to detect vehicle traffic levels at the lanes, this data is received at the controller and transmitted to web server through a Wi-Fi module. The monitored data is stored and analyzed in the server. Here traffic is controlled by traffic signal control method which depends on the detecting traffic levels at the lanes. If any lane gives a high traffic level, then it gives highest priority to passing vehicles. RF transceivers used to communicate the main system to priority system which receives and transmits traffic related message. This system is given at the intersection of lanes which is reliable, simple and low cost.